2009
DOI: 10.1073/pnas.0900121106
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by Cdk2 is required for Myc to repress Ras-induced senescence in cotransformation

Abstract: The MYC and RAS oncogenes are frequently activated in cancer and, together, are sufficient to transform rodent cells. The basis for this cooperativity remains unclear. We found that although Ras interfered with Myc-induced apoptosis, Myc repressed Ras-induced senescence, together abrogating two main barriers of tumorigenesis. Inhibition of cellular senescence required phosphorylation of Myc at Ser-62 by cyclin E/cyclin-dependent kinase (Cdk) 2. Cdk2 interacted with Myc at promoters, where it affected Myc-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(192 citation statements)
references
References 45 publications
17
175
0
Order By: Relevance
“…Moreover, we have shown, by using a unique mouse model that, at near-physiological levels of expression in the mammary gland, the Myc T58A mutant, which lacks T58 phosphorylation and has constitutively high S62 phosphorylation, similar to the phosphorylation pattern we report here in breast cancer, is tumorigenic whereas deregulated nearphysiological levels of WT Myc is not (19). Recent reports have demonstrated that pS62 is important for Myc binding to a number of transactivated target genes important for cell proliferation, growth, and survival (34,35). Thus, increased Myc protein stability and altered T58/S62 phosphorylation are likely to play important roles in breast tumorigenesis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, we have shown, by using a unique mouse model that, at near-physiological levels of expression in the mammary gland, the Myc T58A mutant, which lacks T58 phosphorylation and has constitutively high S62 phosphorylation, similar to the phosphorylation pattern we report here in breast cancer, is tumorigenic whereas deregulated nearphysiological levels of WT Myc is not (19). Recent reports have demonstrated that pS62 is important for Myc binding to a number of transactivated target genes important for cell proliferation, growth, and survival (34,35). Thus, increased Myc protein stability and altered T58/S62 phosphorylation are likely to play important roles in breast tumorigenesis.…”
Section: Discussionsupporting
confidence: 60%
“…Besides affecting Myc protein stability, Myc phosphorylation also affects its oncogenic activity in that the high-pS62 form of Myc is more oncogenic than the form of Myc lacking pS62 (17,19), suggesting an effect of altering this phosphorylation on Myc target gene regulation. Indeed, recent studies in other laboratories and in our laboratory have demonstrated an important role for pS62 in Myc binding to target gene promoters (34,35) (Fig. S7B).…”
Section: Breast Cancer Cells Have a Switch In Axin1 Splice Variant Exmentioning
confidence: 64%
“…CDK2 has also been previously implicated as a possible target to induce senescence, specifically in MYC-transformed cells that have circumvented the senescent response (18). Interestingly, MYC was found to be itself a target of CDK2, and, in cells cotransformed by MYC and RAS, MYC was able to repress RAS-induced senescence, in a manner dependent upon MYC phosphorylation by CDK2 (35). These studies show that CDK2 activity is critical for circumventing senescence during MYC-induced transformation.…”
Section: Ink4amentioning
confidence: 60%
“…8,105,106 For example, landmark studies demonstrated that transformation of primary murine cells with oncogenic Ras require its cooperative interaction with c-Myc. 107 Later findings revealed that activated c-Myc suppresses Ras-induced senescence, 108 whereas oncogenic Ras rescues cells from Myc-induced apoptosis. 8 Notably, the capacity of oncogenes to induce deregulated cell proliferation or promote Cellular senescence.…”
Section: Translational Control Of Cancer Genesismentioning
confidence: 99%